"A mundo valde alieni": Irish Franciscan Responses to the Dissolution of the Monasteries, 1540-1640 - McCafferty, John (Reformation & Renaissance review, 2017)
Henry VIII’s dissolution campaigns affected only about one-fifth of Irish mendicant houses. The Observant friars managed a staged withdrawal to the west and north of the island in the face of later Tudor closures. Drawing on a lengthy history of the Irish friars written in Louvain in 1617, this article explores how the Franciscans responded to the 70-year, slow-motion dissolution of the monasteries. Observants continued to be visibly active in the neighbourhood of many former friaries and were even allowed continued residence within the walls by a number of the new Protestant proprietors. The friars’ ability, as members of an international order, to take a global view of their local exigencies was a key element of their strategy. This article argues that excessive focus on the political dimensions of Reformation in Ireland has occluded proper understanding of the continuities built upon by the Catholic Reformers.